Determinants of tax avoidance with firm size as a moderating variable - Neltiani, Andini; Rusliyawati, Rusliyawati; Astarani, Juanda (WIM Solusi Prima, 2025)
In the context of the growing consumer goods industry, tax avoidance practices are increasingly viewed not only as a means of efficiency but also as an integral part of corporate strategy. This study analyzes the impact of profitability, leverage, and firm age on tax avoidance, while also assessing the role of these three factors in moderating the relationship between firm size and tax avoidance. The research involved a sample of 20 firms in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) during the years 2020 and 2023, with analysis conducted using the Moderated Regression Analysis (MRA) approach and EViews 12 software. The results indicate that profitability and leverage do not significantly affect tax avoidance. Conversely, firm age has been shown to have a positive impact. In the moderation analysis, only firm age serves as a significant moderating variable, while leverage does not. These findings suggest that the age and internal characteristics of a firm exert a more substantial influence on tax strategies compared to other financial ratios. Consequently, tax policies should be formulated with careful consideration of the unique characteristics of the consumer goods sector. This study contributes to the literature on agency theory, as well as to practices in corporate tax management and financial strategy.